2022
DOI: 10.3389/fendo.2022.940675
|View full text |Cite
|
Sign up to set email alerts
|

Associations between COVID-19 infection and sex steroid hormones

Abstract: AimsCoronavirus disease 2019 (COVID-19) is caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and within a few months of the first outbreak, it was declared a global pandemic by the WHO. The lethal virus SARS-CoV-2 is transmitted through respiratory droplets and enters host cells through angiotensin-converting enzyme 2 (ACE-2) receptors. ACE-2 receptors are highly expressed in many tissues, including testes. Therefore, the objective of this study was to summarize the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
3
18
2
Order By: Relevance
“… 19 In line with our results, a systematic review on the level of male sex hormones showed that in patients with severe COVID‐19 infection, the level of total testosterone decreased significantly, and even men with lower levels of testosterone experienced more severe disease and mortality. 20 Similar to our results, Dhindsa et al 11 in a study on 152 hospitalized patients found that men with severe disease had lower levels of testosterone in comparison to men with mild or moderate disease. Consistent with our results, Zeggeren et al 21 in a small study on 40 patients found that the level of total and free testosterone was significantly lower in patients with severe disease and in those who died from severe disease compared to survivors.…”
Section: Discussionsupporting
confidence: 92%
“… 19 In line with our results, a systematic review on the level of male sex hormones showed that in patients with severe COVID‐19 infection, the level of total testosterone decreased significantly, and even men with lower levels of testosterone experienced more severe disease and mortality. 20 Similar to our results, Dhindsa et al 11 in a study on 152 hospitalized patients found that men with severe disease had lower levels of testosterone in comparison to men with mild or moderate disease. Consistent with our results, Zeggeren et al 21 in a small study on 40 patients found that the level of total and free testosterone was significantly lower in patients with severe disease and in those who died from severe disease compared to survivors.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the high prevalence of secondary hypogonadism in all three patient groups could be due to reduced gonadotropin-releasing hormone pulsatility, which is a known phenomenon during acute disease and physiological stress, and may suggest that testosterone concentrations reflect disease severity (27,28,29). Spratt et al studied pituitary-gonadal changes in men undergoing coronary artery bypass graft at pre-admission, during surgery, and the following days post-surgery as a model for acute severe disease (8). As in our study, they found that the study population had decreased concentrations of testosterone, LH, and FSH and increased concentrations of estrone and estradiol as early as the day after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of gonadal hormones differ between sexes, and gonadal and pituitary hormones have been suggested to play a role in disease progression. Studies have reported association of the hypothalamic-pituitary-gonadal (HPG) axis in men hospitalized with COVID-19 with severely suppressed concentrations of testosterone and increased concentrations of estradiol with a reported association to mortality and respiratory failure (2,3,4,5,6,7,8). Additionally, severe COVID-19 is driven by hyperinflammation as reflected by high circulating levels of inflammatory biomarkers such as C-reactive protein (CRP) and interleukin (IL)-6.…”
Section: Introductionmentioning
confidence: 99%
“…FSH, total, free, and bioavailable testosterone levels were lower in patients who required admission to the ICU [34]. Additionally, the greater clinical severity of COVID-19, the higher is the probability of increases in LH, and E2/T serum levels and decreases in SHBG levels [37]. Low SHBG levels were associated with mortality in patients with COVID-19, and low total and free testosterone levels were associated with mortality in men [38].…”
Section: Discussionmentioning
confidence: 99%